2020
DOI: 10.2147/ptt.s270619
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Skin May Clear But the Arthritis Won’t Disappear: Focusing on Concomitant and New-Onset Psoriatic Arthritis in a Daily Practice Cohort of Psoriasis Patients on Biologic Therapy</p>

Abstract: Background Previously identified risk factors for psoriatic arthritis (PsA); nail dystrophy and scalp lesions are highly prevalent in patients with moderate-to-severe psoriasis. Therefore, these variables may not be useful as predictors for PsA in this population. Objective We assessed the predictive value of demographic and clinical characteristics for development of PsA in a cohort of patients with moderate-to-severe psoriasis, currently treated with biologics. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
3
9
2
Order By: Relevance
“…Despite being slightly higher than the results reported by Napolitano et al [22], the percentage of new-onset PsA found in our study is slightly lower than those reported by Van Muijen et al [23], who showed that 32 (9.4%) patients developed PsA during biologic treatment (adalimumab, etanercept, infliximab, ustekinumab, secukinumab) collecting data from the BioCAPTURE database from 1 May 2005 until 1 May 2018. However, their inclusion criteria were different from our study and from those of Napolitano et al [22] concerning the phenotype of psoriasis.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…Despite being slightly higher than the results reported by Napolitano et al [22], the percentage of new-onset PsA found in our study is slightly lower than those reported by Van Muijen et al [23], who showed that 32 (9.4%) patients developed PsA during biologic treatment (adalimumab, etanercept, infliximab, ustekinumab, secukinumab) collecting data from the BioCAPTURE database from 1 May 2005 until 1 May 2018. However, their inclusion criteria were different from our study and from those of Napolitano et al [22] concerning the phenotype of psoriasis.…”
Section: Discussioncontrasting
confidence: 95%
“…Indeed, different studies [22][23][24]34] and real-life experiences [35][36][37][38][39][40][41][42] showed the possibility of PsA onset in patients treated with biologics for psoriasis in 4.5-9.4% of cases [22,24]. The present study aims to evaluate the incidence of new-onset PsA in patients with plaque psoriasis on anti-TNFα (adalimumab, certolizumab, etanercept, infliximab), anti-IL12/23 (ustekinumab), anti-IL23 (risankizumab, tildrakizumab, guselkumab) or anti-IL17 (brodalumab, ixekizumab, secukinumab) therapy attending our Dermatology Unit and undergoing at least 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations